THE EFFECTIVENESS OF COMBINED HYPERBARIC OXYGEN THERAPY WITH OTHER METHODS IN THE TREATMENT OF ISCHEMIC STROKE PATIENTS AT MILITARY HOSPITAL 103 - Bùi, Tuấn; Dinh Thi Van Anh; Hoang Tien Ung (Tạp chí Y học Quân sự, 2025)
Objectives: To evaluate the effectiveness of combined hyperbaric oxygen therapy with other methods in the treatment of ischemic stroke patients. Subjects and methods: An uncontrolled interventional study conducted on 30 ischemic stroke patients treated at the Department of Rehabilitation, Military Hospital 103, from September 2023 to August 2024. Muscle strength was assessed using the MRC scale. Independence in activities of daily living was evaluated using the Barthel scale. Neurological impairment was assessed using the NIHSS scale. Results: The proportion of patients with muscle strength grade 1 (40.0%) and grade 2 (40.0%) before treatment significantly decreased after treatment (to 20% and 20%, respectively), with a p-value < 0.05. Patients' independence in daily activities before treatment (100% dependent; of which 40.0% were completely dependent, 60.0% partially dependent) showed statistically significant improvement. After treatment, no patients remained completely dependent; 66.7% were still partially dependent, 20% were independent, and 13.3% were fully independent (p < 0.05). The mean NIHSS score significantly decreased from 6.98 ± 2.12 before treatment to 4.23 ± 0.89 after treatment (p < 0.05). Conclusion: There was a positive improvement in muscle strength, daily activity function, and cognitive function according to the NIHSS in ischemic stroke patients receiving adjunctive hyperbaric oxygen therapy.